Bounded in Art, Connected by Culture: Pentas Budaya Berbahasa Inggris sebagai Model Penguatan Intercultural Communicative Competence dan Cross-cultural Awareness - Tri Pujiani; Muhammad Soali; Nisa Roiyasa; Ida Dian Sukmawati (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2026)
The necessity to enhance university students' proficiency in public English-speaking and intercultural awareness is becoming progressively critical, especially as numerous students may grasp fundamental language structures but lack the confidence to articulate cultural and literary concepts persuasively in public contexts. In response to this challenge, the community devotion program established a learning-by-performing approach through an English-medium cultural showcase and a wayang-themed theatrical performance titled “Bounded in Art, Connected by Culture”. The event took place on 19 December 2025 at Campus 2 of Universitas Harapan Bangsa, Purwokerto, as a collaboration between the English Education Study Program, Faculty of Social Sciences, and the Sanggar Kie Bae community arts group. The participants comprised nine faculty members, 52 students from the Faculty of Social Sciences, students from four partner universities (five from each institution), and eight international students from Sudan, Nigeria, the Republic of the Congo, Zimbabwe, Cambodia, and Cameroon. The program included Indonesian cultural performances, presentations of international students' home cultures, an English-language theatrical performance of the